Five-minute activities : - Ur, Penny (Cambridge University Press, 1992)
Five-minute Activities contains over 130 ideas for the foreign language classroom in its 100 pages. I read this book from cover to cover, and was pleased to be able to make many notes for my future lessons. Some of the activities are actually quite common, and perhaps most teachers would be aware of them, but there were many good ones that I'd never come across, including a few gems